2014
DOI: 10.2217/bmm.14.41
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of PITX2 Predicts Poor Survival in Men with Prostate Cancer

Abstract: Our study strengthens prior findings that PITX2 methylation is useful as a biomarker of poor outcome of PCa and in addition we also suggest that it may be particularly useful in men with low Gleason score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Methylation data from 367 patients was obtained from previous studies [11, 12]. Methylation measurements for HSPB1, CCND2, TIG1, DPYS, PITX2, and MAL were performed on bisulfite converted DNA from an additional 352 patients as previously described [11, 12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation data from 367 patients was obtained from previous studies [11, 12]. Methylation measurements for HSPB1, CCND2, TIG1, DPYS, PITX2, and MAL were performed on bisulfite converted DNA from an additional 352 patients as previously described [11, 12].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent report, we demonstrated that changes in methylation of HSPB1, CCND2 , TIG1, DPYS , and, MAL, had significant prognostic effects in multivariate Cox models where death from prostate cancer was the study endpoint [11]. In an additional matched case-control study using a subset of patients with low and intermediate Gleason score, methylation of the PITX2 gene was informative for identification of men at high risk of aggressive prostate cancer [12]. Here we propose a new risk stratification score utilizing the methylation levels of the six genes: HSPB1, CCND2, TIG1, DPYS, PITX2, and MAL, that enhance identification of men with aggressive cancer who would otherwise be considered of low or intermediate risk based on clinical variables.…”
Section: Introductionmentioning
confidence: 99%
“…90 For prostate cancer, a variety of genes has been suggested as prognostic methylation marker in smaller studies with PITX2 being most extensively verified so far. [91][92][93][94][95][96][97][98][99] A commercialized diagnostic test, that measures gene methylation in tissues of an initial negative biopsy to estimate the likelihood of a cancer diagnosis on subsequent biopsy is the ConfirmDX test (MDx Health). The histological demonstration of carcinoma is still the diagnostic gold standard to allow for curative therapy.…”
Section: Dna-methylationmentioning
confidence: 99%
“…The same phenomenon has been shown for NSCLC [28], a tumor which, like HNSCC, is known for its strong association with a history of smoking. Interestingly, in hormonally dependent tumors like breast and prostate cancer, PITX2 DNA hypermethylation has been associated with adverse overall survival [2527, 29]. This might point at a role of PITX2 in tumorigenesis which lies beyond cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therawis GmbH (Munich, Germany) in collaboration with Qiagen N.V. (Venlo, The Netherlands) have recently announced the development of a commercially available assay exploiting the additional predictive potential of PITX2 methylation in breast cancer patients. In prostate cancer, PITX2 hypermethylation has been associated with biochemical recurrence, contributing to individualized risk assessment as a single assay and in combination with PITX3 methylation analysis [20, 2223, 29]. In addition to its known role in the development of several organs, PITX2 also mediates cell cycle progression by regulating the transcription of cyclin A1, cyclin D2, and p21, therefore providing sufficient evidence to implicate PITX2 in tumorigenesis [3032].…”
Section: Introductionmentioning
confidence: 99%